The Effect of Prenatal Yoga on Birth Labor Duration and Pain: A Meta Analysis - Riawati, Meida Siwi; Budihastuti, Uki Retno; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Increased psychological burden during pregnancy can cause problems with the quality of the fetus and cause complications in pregnancy. The lack of knowledge about labor pain management and the mother's perception of prolonged labor makes the mother experience an increase in the psychological burden during pregnancy. One alternative therapy needed in dealing with a happy pregnancy and minimal trauma delivery is to do prenatal yoga. The purpose of this study was to estimate the magnitude of the effect of prenatal yoga on the duration of labor and labor pain. Subjects and Method: This study uses a systematic review and meta-analysis research design. The time of the selected test results is between 2005 to 2021. The search for articles is carried out for 1 month. Research data was searched from databases: PubMed, Science Direct, Springer Link, Google Scholar, Chocrance Library. The inclusion criteria in this study were full text articles in English, the study design used a randomized controlled trial. Article searches were carried out using the PICO model. The population in this study were pregnant women, the intervention was in the form of prenatal yoga, comparison was without prenatal yoga, and the outcomes were labor duration and labor pain. Data processing is carried out using the Review Manager (RevMan 5.3) by calculating the standardized mean difference to determine the combined research model and form the final result of the meta-analysis. Results: There are 9 articles in the study of the effect of prenatal yoga on the duration of labor and there are 5 articles on labor pain. The study showed that prenatal yoga significantly reduced labor duration (SMD= 0.88; 86% CI -1.31 to -0.44 p<0.001). Prenatal yoga can also reduce labor pain (SMD = 0.88; 77% CI -1.44 to -0.33 p = 0.002). Conclusion: Prenatal yoga can reduce labor duration and reduce labor pain.